Transient receptor potential channel 6 knockdown prevents apoptosis of renal tubular epithelial cells upon oxidative stress via autophagy activation - Hou, Xin (2018)
Fil: Hou, Xin. Huazhong University of Science and Technology. Tongji Medical College. Department of Anatomy; China